Supporting student wellbeing in school contexts: A narrative review - Dempsey, Caoimhe; McCoy, Selina (ESRI, 2026)
International and Irish studies have indicated negative trends in the mental health and wellbeing of young people over recent years. Indeed, the most recent wave of the Health Behaviour of School-Aged Children study shows that Ireland ranked 24 out of 36 countries on overall adolescent mental health. This is in stark contrast to Ireland’s high rankings on adolescent academic and social skills (1st) and physical health (11th) within the study (Cosma et al., 2023). In the face of these worrying trends, in many countries, including Ireland, there is a growing awareness that wellbeing is both an outcome and an enabler of learning, such that academic goals can only be addressed within the context of positive wellbeing. The psychosocial environment in schools is critical for fostering students’ emotional and social wellbeing. Schools hold significant potential to promote wellbeing and mental health given their capacity to (a) reach diverse young people, (b) facilitate social connections and (c) host wide-ranging interventions. Indeed, children and adolescents themselves describe school as having a large impact on their wellbeing (ONS, 2020). Ireland has made significant strides in promoting student wellbeing and mental health in schools in recent years. The Department of Education and Youth’s approach to supporting both wellbeing and mental health in schools and educational contexts is set out in its Wellbeing Policy Statement and Framework for Practice (2018), and is evaluated at school level through the school self-evaluation process. However, despite these policy strides, significant concerns and disagreement remain regarding how best to promote and even monitor student wellbeing and mental health in school contexts. Addressing this issue, the current review adopts a narrative approach to exploring how wellbeing and mental health are promoted and monitored in school contexts in Ireland and internationally. A broad range of literature underpins the findings presented, including quantitative and qualitative empirical articles, policy reports, government agency documents and publications from international organisations (e.g., UNESCO, OECD). Together these sources ensure a wide range of insights from various disciplines. The findings from this evidence base provide the basis for recommendations on how the Irish Wellbeing Policy Statement and Framework for Practice could be further developed.